2014
DOI: 10.1080/17445302.2014.985430
|View full text |Cite
|
Sign up to set email alerts
|

Empirical formulations for estimation of ultimate strength of continuous aluminium stiffened plates under combined transverse compression and lateral pressure

Abstract: Empirical expressions are developed for predicting ultimate compressive strength of welded aluminium stiffened plates used in marine applications under combined transverse in-plane compression and different levels of lateral pressure. A database of the ultimate transverse strengths for aluminium stiffened plates numerically obtained by the authors is used for deriving formulations as functions of two parameters, namely the plate slenderness ratio and the column (stiffener) slenderness ratio. Regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
(21 reference statements)
2
7
0
Order By: Relevance
“…As it was already stated, the current study is a continuation of the work reported in Khedmati et al (2010bKhedmati et al ( , 2014b. Thus, its results are fully supported by the numerous validation analyses already performed by Khedmati et al (2009).…”
Section: Validation Of Numerical Modelsupporting
confidence: 76%
See 1 more Smart Citation
“…As it was already stated, the current study is a continuation of the work reported in Khedmati et al (2010bKhedmati et al ( , 2014b. Thus, its results are fully supported by the numerous validation analyses already performed by Khedmati et al (2009).…”
Section: Validation Of Numerical Modelsupporting
confidence: 76%
“…Later, empirical formulations for estimation of ultimate strength of continuous stiffened aluminium plates under combined longitudinal in-plane compression and lateral pressure were derived by Khedmati et al (2010b). Also, Khedmati et al (2014b) extended their empirical formulations to the case of continuous stiffened aluminium plates under combined transverse in-plane compression and lateral pressure This paper is a continuation of the studies made by Khedmati et al (2010bKhedmati et al ( , 2014b, in order to further develop empirical formulations for prediction of ultimate strength of continuous stiffened aluminium plates under combined biaxial in-plane compression and lateral pressure. The ultimate compressive strength data numerically obtained by the authors is used for deriving the formulations which are expressed as functions of two parameters, namely the plate slenderness ratio and the column (stiffener) slenderness ratio.…”
Section: Introductionmentioning
confidence: 99%
“…where B x , B y and H are defined based on the cross-section of the panel and L/b is the aspect ratio. Khedmati et al (2014) extended the formulation suggested in Khedmati et al (2010b) for stiffened plates subjected to combined lateral pressure and axial inplane compression. A series of FE analyses, with different types of stiffener (flat, angle and tee bar) and with a wide range of slenderness ratios, were performed considering both initial imperfections and HAZ.…”
Section: Empirical and Analytical Methodsmentioning
confidence: 97%
“…Several numerical investigations have been performed to simulate the experimental tests and/or to derive the database for regression analyses to establish different empirical formulations (Paik 2007a(Paik , 2007bPaik et al 2008Paik et al , 2012Khedmati et al 2010bKhedmati et al , 2014. Khedmati and Ghavami (2009) analysed the buckling and ultimate strength behaviour of stiffened aluminium panels with fixed or floating transverse frames.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…This paper deals with the ultimate limit state of a steelstiffened plate structure under uniaxial compresive loads. A number of useful studies on the ultimate strength of plate panels for marine applications are found in the literature (Abdussamie et al 2018;Benson et al 2011;Gannon et al 2013Gannon et al , 2016Iijima et al 2015;Jagite et al 2019Jagite et al , 2020Khan and Zhang 2011;Khedmati et al 2014Khedmati et al , 2016Kim et al 2009Kim et al , 2015Kumar et al 2009;Lee and Paik 2020;Magoga and Flockhart 2014;Ozguc et al 2006;Paik 2007;Paik et al 2013;Rahbar-Ranji and Zarookoan 2015;Ringsberg et al 2018;Shi and Gao 2020;Shi and Wang 2012;Zhang 2016;Wang et al 2009). For plate panels of engineering structures with variable or nonuniform thickness, the structural responses should be characterized by taking into account the effects of variable thickness.…”
Section: Introductionmentioning
confidence: 99%